2021
DOI: 10.3390/plants10122659
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Endophytic Talaromyces pinophilus on Growth, Absorption and Accumulation of Heavy Metals of Triticum aestivum Grown on Sandy Soil Amended by Sewage Sludge

Abstract: Sewage sludge improves agricultural soil and plant growth, but there are risks associated with its use, including high heavy metal content. In this study, experiments were carried out to investigate the role of endophytic Talaromyces pinophilus MW695526 on the growth of Triticum aestivum cultivated in soil amended with sewage sludge and its phytoremediation ability. T. pinophilus could produce gibberellic acid (GA) and stimulate T. aestivum to accumulate GA. The results showed that inoculation with T. pinophil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 84 publications
(82 reference statements)
2
10
0
1
Order By: Relevance
“…Different studies have found a decrease in growth parameters as a result of heavy metal stress (Tiwari and Lata 2018). Our data are compatible with those of (Shahid et al 2015;El-Shahir et al 2021), who discovered that heavy metal stress significantly reduced plant height, root length, fresh and dry weights of shoots and roots. Heavy metal binds to the cell wall and the middle lamellae, enhancing pectin cross-linking and contributing to growth reduction, as well as to the plant as a whole (Khan et al 2017).…”
Section: Discussionsupporting
confidence: 92%
“…Different studies have found a decrease in growth parameters as a result of heavy metal stress (Tiwari and Lata 2018). Our data are compatible with those of (Shahid et al 2015;El-Shahir et al 2021), who discovered that heavy metal stress significantly reduced plant height, root length, fresh and dry weights of shoots and roots. Heavy metal binds to the cell wall and the middle lamellae, enhancing pectin cross-linking and contributing to growth reduction, as well as to the plant as a whole (Khan et al 2017).…”
Section: Discussionsupporting
confidence: 92%
“…Talaromyces pinophilus , a fungus from the genus Talaromyces and the family Trichocomaceae is known for producing some essential bioactive metabolites, including terpenoids, alkaloids, polyketides, tetraene, esters, lactones, and furanosteroids [ 5 7 ]. This fungal species has been widely employed as effective cellulose and waste degrading agent [ 8 , 9 ], a renewable source of natural colourants [ 10 ], and a stimulator of phytoremediation efficacy [ 11 ]. Furthermore, T. pinophilus exhibited plant development-promoting properties on Waito-C rice [ 12 ] and chickpea [ 13 ], as well as mycoparasitic activity against Botrytis cinerea [ 14 ] and Rhizoctonia solani [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Toxicity of arsenic in Brassica juncea is reduced by Staphylococcus arlettae via enhanced production of dehydrogenase and phosphatase enzyme in soil (Srivastava et al, 2013 ). Inoculation of Talaromyces pinophilus in Triticum aestivum plants stimulates plant growth via the production of gibberellic acid under heavy metal stress (El-Shahir et al, 2021 ). Paredes-Páliz et al ( 2018 ) reported that inoculation of metal-resistant bacteria such as B. aryabhattai and Pantoea agglomerans brings production of phenylalanine ammonia-lyase enzyme and SOD which protects plants from metal stress.…”
Section: Role Of Biofertilizers In Abiotic Stress Managementmentioning
confidence: 99%